The Effect Of Student’s Personality Perception And Language Learning Strategy Towards Speaking Skill (Survey At State Junior High School In North Jakarta) - Pujiani, Lilik; Herlyna, Herlyna (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2025)
This study aimed to examine the effects of Student’s Personality Perception and language Learning Strategy towards Speaking Skill. This research is conducted at SMPN 84 and SMPN 279, North Jakarta. The method of the research was a descriptive survey using some samples from the number of the population and using test instrument for data collection. The hypothesis test showed that: 1). There are any significant effects of the Student’s Personality Perception and Language Learning Strategy towards Speaking Skill at the state of Junior High School in North Jakarta. That is proved by the score of Sig. 0.02 < 0.05 and Fo = 2,454. Both variables have given a contribution of 75.5% to the speaking skill. 2). There is a significant effect of student’s personality perception towards speaking skill at the state of junior High School in North Jakarta. That is proved by the score of Sig. = 0.02 < 0.05 and to = 3,182. Student’s personality perception has given a contribution of 69.2% to the Speaking Skill 3). There is a significant effect of the Language learning Strategy towards speaking skill at the state junior School in North Jakarta. That was proved by the score of Sig. = 0.01 < 0.05 and to = 3.621. The Language Learning Strategy had given a contribution of 64.8% to Speaking Skill. Based on the result of the research, it proves that personality perception gives higher contribution on speaking skill than Language Learning Strategy.